2012
DOI: 10.1111/j.1600-048x.2012.05651.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation and the evolution of song in Mesoamerican rufous‐naped wrensCampylorhynchus rufinucha

Abstract: Speciation may be influenced by geographic variation in animal signals, particularly when those signals are important in reproductive decisions. Here, we describe patterns of geographic variation in the song of rufous-naped wrens Campylorhynchus rufinucha. This species complex is a morphologically variable taxon confined to tropical dry forest areas from Mexico to northwestern Costa Rica. Morphological and genetic analyses suggest that there are at least three partially isolated groups within the complex, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Our results, however, show that divergence in learned signals may not occur as rapidly as is sometimes thought (discussed in Price & Lanyon, ). Our results are in line with other studies that show a parallel divergence between songs and genetics in other oscine bird species (Price & Lanyon, ; Farnsworth & Lovette, ; Irwin et al ., ; Cadena & Cuervo, ; Sosa‐López et al ., ), suggesting a bias for learning the song of the parental population and perhaps a partially genetically controlled sound production system (Remsen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, however, show that divergence in learned signals may not occur as rapidly as is sometimes thought (discussed in Price & Lanyon, ). Our results are in line with other studies that show a parallel divergence between songs and genetics in other oscine bird species (Price & Lanyon, ; Farnsworth & Lovette, ; Irwin et al ., ; Cadena & Cuervo, ; Sosa‐López et al ., ), suggesting a bias for learning the song of the parental population and perhaps a partially genetically controlled sound production system (Remsen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have revealed that variation in acoustic signals parallels phylogenetic relationships (e.g. Ryan & Rand, 1999;Johnson et al, 2000;de Kort & ten Cate, 2001;Price & Lanyon, 2002;Ord & Martins, 2006;Percy et al, 2006;Farnsworth & Lovette, 2008;Irwin et al, 2008;Sosa-L opez et al, 2013; but see Price et al, 2007), suggesting that acoustic signals have phylogenetically conserved components. However, the evolutionary processes that drive animal perception of phylogenetically conserved components of acoustic signals are not well studied (Irwin & Price, 1999;Grether, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found significant acoustic differences among three allopatric populations in the superciliosus group (Pacific, Chiapas, and Central America). Divergence in acoustic traits has been found to occur widely among allopatric populations (e.g., Toews and Irwin , Cadena and Cuervo , Chaves et al , Sosa‐López et al , Sosa‐López and Mennill , Ortiz‐Ramírez et al , Sandoval et al ). For example, geographic isolation of Wedge‐tailed Sabrewings ( Campylopterus curvipennis ) driven by paleoclimatic historical events might explain the vocal, genetic, and morphological differentiation exhibited by allopatric populations (González et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Divergence in learned songs could have evolved due to selective (e.g., cultural selection, natural selection, or through selection on song as a social and sexual signal) and/or non‐selective factors (e.g., cultural drift and genetic drift; Wilkins et al ). Variation in learned songs is also influenced by the evolutionary history of a species, with a number of studies providing evidence of corresponding variation between song and genetic divergence, e.g., Pacific Wren ( Troglodytes pacificus ) vs. Winter Wren ( T. hiemalis ; Toews and Irwin ), Rufous‐naped Wren ( Campylorhynchus rufinucha ; Vázquez‐Miranda et al , Sosa‐López et al ), White‐browed Brush‐finch ( Arremon torquatus ; Cadena and Cuervo ), Wedge‐tailed Sabrewing ( Campylopterus curvipennis ; González et al ), White‐crowned Sparrow ( Zonotrichia leucophrys ; Lipshutz et al ), and Timberline Wren ( Thryorchilus browni ; Camacho‐Alpízar et al ), and concordance between vocal traits and phylogenetic relationships (e.g., McCracken and Sheldon , Price and Lanyon ).…”
mentioning
confidence: 99%
See 1 more Smart Citation